Thyroid Dysfunction among Patients with Diabetes Mellitus in Kathmandu - Bhusal, Khema Raj; Pokhrel, Pratap; Simkhada, Rabindra (Journal of College of Medical Sciences-Nepal, 2018)
Background: This study was conducted with the objective of studying thyroid dysfunction in patients with diabetes mellitus. Materials & Methods: A total 100 patients consisting of 40males and60females diagnosed as diabeteswere included in the study. Laboratory values of different thyroid parameters were taken. Results: Among the participants 60% were female and 40% were male.Age ranged from 17to 88 years with mean being 55.73 ± 1.62years. Presence of thyroid dysfunction was found in35% of the cases. Subclinical hypothyroidism was found in20%of participants, frank hypothyroidism in10%, subclinical hyperthyroidism in 3% and frank hyperthyroidism in2%. Conclusion: This study showed the high prevalence of thyroid dysfunction in patients with diabetes mellitus. Early testing for thyroid function is very useful to detectdysthyroidism in all diabetic patients Keywords: diabetes; thyroid dysfunction; subclinical hypothyroidism.